Peningkatan Hasil Belajar Siswa Menggunakan Metode PBL dengan Bantuan Problem Solving Fase F SMA N egri 1 S irombu - Rosmafiti Hia; Nerita Setiyaningtiyas; Tarsisius Adi Prasetya (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education for human life is an absolute necessity that must be fulfilled throughout life. Without education, it is completely impossible for a group of people to live and develop in line with their aspirations (ideals) to progress, prosper, and be happy according to the concept of their outlook on life. According to the National Education System Law No. 20 of 2003 (2003, p. 1) states: Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. National Education functions to develop abilities and shape the character and civilization of a dignified nation in order to educate the life of the nation, aiming to develop the potential of students to become Marusia who believes in and fears God Almighty, has noble character, is healthy, knowledgeable, capable, creative, independent, and becomes a democratic and responsible citizen (National Education System Law No. 20 of 2003). The independent curriculum emphasizes the profile of Pancasila students. In this class action research, the researcher focuses on the dimension of independence which is based on the importance of character formation and a strong mental attitude in the younger generation, especially in facing complex global challenges. The students who are accepted to attend SMA Negeri 1 Sirombu are students who are accepted into majors that do not match their initial interests. Students with this kind of condition tend to feel unmotivated to learn. Based on the conditions of the above problems, teachers can provide a learning experience by designing the learning process. One of the learning models that can be applied is Problem Based Learning (PBL) or problem-based learning. The objectives of the research include (1) to find out how to use the Problem Based Learning model in increasing students' learning motivation on diversity material as the original reality of human life in grade XII of SMA Negeri 1 Sirombu, (2) to determine the increase in learning motivation of students in grade XII of SMA Negeri 1 Sirombu with the help of the Problem Based Learning modelon unique personal materials as equal men and women, (3) to find out the use of the Problem Based Learning model on diversity materials as the original reality of life, students in grade XII of SMA Negeri 1 Sirombu can apply the Pancasila student profile of the independence dimension. The type of research used is qualitative with a descriptive approach. The data collection technique in this study uses observation, interviews and documentation. The data analysis techniques used consist of data reduction by selecting raw data into information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from the results of the research that refer to the formulation of the problem. The use of the Problem Based Learning model according to the syntax which includes orientation of students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem-solving process, effective in helping to increase learning motivation and students' independence in diversity material as the inherent reality of human life in grade XII of SMA Negeri 1 Sirombu.